Living Streets : Strategies for Crafting Public Space. - Bain, Lesley (John Wiley & Sons, 2012)
Written for teams of engineers, transportation planners, landscape architects, and urban planners, this book provides a broad overview of the growing approach towards complete and sustainable street design. Its contents present the background on modern street design and where it has failed, describe a series of street typologies, and demonstrate, through geographically diverse case studies, the applicable lessons learned from each. Featuring examples from over two dozen completed street design projects around the world, it provides practical guidance on the complete street approach to sustaina.